Meniscal injuries in the Olympic and elite athletes - Vaishya, R.; Kambhampati, S. B. S.; Vaish, A. (Indian Journal of Orthopaedics, 2020)
Introduction Elite and Olympian athletes are often stretching the upper limits of normal physiology and biomechanics of the musculoskeletal system in their efforts to excel in their sport. For them to get back to their sport at the same level after injury, the management, repair techniques, and rehabilitation protocols should be robust to permit healing of tissues to allow supra-normal loading and performance. The knee and the meniscus are commonly injured in these sports. Yet, the incidence, mechanisms, types of injuries to the meniscus, and their management are not known across different sports in the Olympics. Methods We set out to look into the incidence and the trends of publications on meniscal injuries of the knee in Olympic games. A search of the PubMed and Scopus for these injuries using a search strategy gave 79 and 116 articles, respectively. Results There were very few publications giving the incidence of meniscal injuries in the Olympics. Football is the sport with the highest rate of meniscal injuries. Different sports are popular in different countries, and depending on the popularity and the country reporting these injuries, incidences differed. There was data available from India and Brazil for Elite athlete from diverse sports, whereas most data from other countries were for football and soccer. Knee was found to be the second most commonly injured part of the body in both Winter and Summer Olympics as well as the Youth Winter Olympics. Data were not available from the Youth Summer Olympics to make any conclusions. The number of publications on this topic is low. We presented the timeline of publications and citations of articles on this topic. The top country, language, journal, university, and author were USA, English, American Journal of Sports Medicine, Hospital of Special Surgery in New York and Brophy RH, respectively. The data on the risk factors for meniscal injuries were analyzed, discussed, and presented for football, as this was the most extensively studied sport. Conclusions Even though the knee is one of the commonly injured anatomical locations in elite athletes, there is a lack of literature on meniscal injuries in this subset of population. We looked at possible reasons and made recommendations to improve data collection on these injuries.